Refining dual-energy x-ray absorptiometry data to predict mortality among cirrhotic outpatients: A retrospective study - Amaral Santos, Livia Alves [UNESP]; Lima, Talles Bazeia [UNESP]; Qi, Xingshun; Rupp de Paiva, Sergio Alberto [UNESP]; Romeiro, Fernando Gomes [UNESP] (Elsevier B.V., 2021)
Objective: The aim of this study was to compare the effects of muscle wasting according to measures obtained by different limb muscle mass indexes, to find the best mortality predictor among outpatients with cirrhosis. Methods: Patients with liver cirrhosis (N = 210) were submitted to dual-energy x-ray absorptiometry (DXA). Appendicular muscle mass (AMM), AMM index (AMMI), upper limb muscle mass (ULMM), and ULMM index (ULMMI) were calculated. The Model for End-Stage Liver Disease, anthropometric measures, and the presence of ascites and edema were also registered. Multiple logistic regressions were performed to determine mortality predictors; the area under the receiver operating characteristic curve was used to establish the best cutoff point to predict mortality. Results: The mean follow-up duration was 49 & sect; 15.59 mo. ULMM and ULMMI were clearly associated with mortality (P = 0.007 and 0.001, respectively), whereas AMM and AMMI were not. After calculating the cutoff points for men and women, the presence of a depleted ULMMI as a categorical variable was associated with a mortality risk 2.5 times higher. Conclusions: The results suggest that using ULMMI is better than AMMI for predicting mortality of outpatients with cirrhosis, thus offering a better measure to detect muscle wasting in this population using DXA. (c) 2020 Elsevier Inc. All rights reserved.
Keywords: Liver cirrhosis; Sarcopenia; Dual-energy x-ray absorptiometry; Mortality; Edema; Ascites